2014
DOI: 10.1021/ma402325a
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylenimine)-Based Polymer Blends as Single-Ion Lithium Conductors

Abstract: Highly conductive solid polymer electrolytes were generated by blending linear poly(ethyleneimine)-graftpoly(ethylene glycol) with linear poly(ethyleneimine) bearing lithium N-propylsulfonate groups as the lithium source. The effect of polymer backbone structure on Li + conductivity was determined by comparing a series of blends made from the PEI-based materials with those from polymethacrylate backbone analogues. The use of PEI backbones promoted ion-pair dissociation, stabilized the macromolecular mix and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…The buildup of anions on the anode results in electropolarization, which lowering the overall performance of LIBs due to high internal resistance, voltage losses, and undesirable side reactions. 557 Single-ion conductors can overcome most of these challenges. However, the lower ionic conductivities (< 10 -5 S cm -1 ) are obtained in these single-ion systems when compared with salt-doped counterparts, which resulting from the covalent bonding of the anions to the polymer backbone and to an incomplete dissociation of the lithium salts within the polymer matrix.…”
Section: Peo-based Single-ion Electrolytesmentioning
confidence: 99%
“…The buildup of anions on the anode results in electropolarization, which lowering the overall performance of LIBs due to high internal resistance, voltage losses, and undesirable side reactions. 557 Single-ion conductors can overcome most of these challenges. However, the lower ionic conductivities (< 10 -5 S cm -1 ) are obtained in these single-ion systems when compared with salt-doped counterparts, which resulting from the covalent bonding of the anions to the polymer backbone and to an incomplete dissociation of the lithium salts within the polymer matrix.…”
Section: Peo-based Single-ion Electrolytesmentioning
confidence: 99%
“…These results are one of very few examples clearly demonstrating that the prepared single-ion membrane is applicable for use in lithium-ion batteries at room temperature. 32 …”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…29 A group of single-ion conductors comprising poly(ethylenimine)-based polymer blends has been reported to show a state-of-the-art conductivity of 4 × 10 −4 S cm −1 at ambient temperature. 32 Another class of single-ion conductors is gel polymer electrolytes, which have been reported to display ionic conductivities of 10 −6 ∼10 −3 S cm −1 at room temperature. 33−42 Watanabe et al reported a blend of polymeric lithium salts and polyether networks, which reached an ionic conductivity of 10 −4 S cm −1 when plasticized with ethylene carbonate (EC).…”
Section: Introductionmentioning
confidence: 99%
“…Lithium battery electrolytes (LIBs), which are generally all dual‐ion systems, including positive and negatively charged ions. Dual‐ion systems generally have lower cation transference numbers (0.3–0.5) and movement of both the ions leads to electrode polarization . One of the main objectives behind constructing a single‐ion system is potentially eliminating the aforementioned flaws and enhancing lithium ion battery performance.…”
Section: Introductionmentioning
confidence: 99%